In Vitro Antimicrobial Activity of Essential Oil of Thymus schimperi, Matricaria chamomilla, Eucalyptus globulus, and Rosmarinus officinalis. (4th January 2016) - Mekonnen, Awol; Yitayew, Berhanu; Tesema, Alemnesh; Taddese, Solomon
Abstract : In this study, the in vitro antimicrobial activities of four plant essential oils ( T. schimperi, E. globulus, R. officinalis, and M. Chamomilla ) were evaluated against bacteria and fungi. The studies were carried out using agar diffusion method for screening the most effective essential oils and agar dilution to determine minimum inhibitory concentration of the essential oils. Results of this study revealed that essential oils of T. schimperi, E. globulus, and R. officinalis were active against bacteria and some fungi. The antimicrobial effect of M. chamomilla was found to be weaker and did not show any antimicrobial activity. The minimum inhibitory concentration values of T. schimperi were< 15.75 mg/mL for most of the bacteria and fungi used in this study. The minimum inhibitory concentration values of the other essential oils were in the range of 15.75–36.33 mg/mL against tested bacteria. This study highlighted the antimicrobial activity of the essential oil of E. globulus, M. chamomilla, T. Schimperi, and R. officinalis . The results indicated that T. schimperi have shown strong antimicrobial activity which could be potential candidates for preparation of antimicrobial drug preparation.